Innovative approach for removal and biodegradation of contaminated compounds in soil by cyclodextins - Hidefumi Yoshii; Yuuki Kugimoto; Takeshi Furuta; Sinichiro Nakayasu; Jjunji Shimizu; Teruaki Arai; Pekka Linko (ՀՀ ԳԱԱ հրատ.)
Hydroxypropyl-β-cyclodextrin (HP-β-CD)was used for the remediation of contaminated soil.
Keywords: Biology; Biochemistry